Intelligent demand side management technique for industrial consumer - Hamid, E. (IEEE Computer Society, 2014)
Electrical demand is continuously increasing due to technologies, and hence the supply-demand gap is also increasing. Under such circumstances, Demand Side management is applied to manage the load demand and minimize the energy consumption. The objective of this paper proposes a fuzzy multi criterion decision-making system as an intelligent system for demand side management technique for efficient energy and energy saving in industrial building. Â© 2014 IEEE.